(untitled) (Journal of Hama University, 2021)
The aim of this study is to extraction the psychometric properties the scale of quality of family life, by usef ali. For this purpose, we have chosen a sample of (274) students (boys and girls) from hama university, they were chosen random sample. We have applied two methods: half dividing and the internal coherence method through counting Alpha cronback. . The validity of scale was confirmed by: (the content validity, criterion related validity significance the comparison peripheral believe, and the structural validity through the study of the internal coherence of the scale and the procedure of factorial analysis). Using the above mentioned statistical styles we have reached that the measurement of quality of family life realized accepted levels of validity and reliability after it has been applied with a sample of students at university, that its characteristics agree with successful evaluation feature.